Biomarkers for Systemic Therapy in Metastatic Breast Cancer: ASCO Guideline Update. Issue 27 (20th September 2022) - Henry, N. Lynn; Somerfield, Mark R.; Dayao, Zoneddy; Elias, Anthony; Kalinsky, Kevin; McShane, Lisa M.; Moy, Beverly; Park, Ben Ho; Shanahan, Kelly M.; Sharma, Priyanka; Shatsky, Rebecca; Stringer-Reasor, Erica; et al.
Abstract : PURPOSE: To update the ASCO Biomarkers to Guide Systemic Therapy for Metastatic Breast Cancer (MBC) guideline. METHODS: An Expert Panel conducted a systematic review to identify randomized clinical trials and prospective-retrospective studies from January 2015 to January 2022. RESULTS: The search identified 19 studies informing the evidence base. RECOMMENDATIONS: Candidates for a regimen with a phosphatidylinositol 3-kinase inhibitor and hormonal therapy should undergo testing for PIK3CA mutations using next-generation sequencing of tumor tissue or circulating tumor DNA (ctDNA) in plasma to determine eligibility for alpelisib plus fulvestrant. If no mutation is found in ctDNA, testing in tumor tissue, if available, should be used. Patients who are candidates for poly (ADP-ribose) polymerase (PARP) inhibitor therapy should undergo testing for germline BRCA1 and BRCA2 pathogenic or likely pathogenic mutations to determine eligibility for a PARP inhibitor. There is insufficient evidence for or against testing for a germline PALB2 pathogenic variant to determine eligibility for PARP inhibitor therapy in the metastatic setting. Candidates for immune checkpoint inhibitor therapy should undergo testing for expression of programmed cell death ligand-1 in the tumor and immune cells to determine eligibility for treatment with pembrolizumab plus chemotherapy. Candidates for an immune checkpoint inhibitor should also undergo testing for deficient mismatch repair/microsatellite instability-high to determine eligibility for dostarlimab-gxly or pembrolizumab, as well as testing for tumor mutational burden. Clinicians may test for NTRK fusions to determine eligibility for TRK inhibitors. There are insufficient data to recommend routine testing of tumors for ESR1 mutations, for homologous recombination deficiency, or for TROP2 expression to guide MBC therapy selection. There are insufficient data to recommend routine use of ctDNA or circulating tumor cells to monitor response to therapy among patients with MBC. Additional information can be found at www.asco.org/breast-cancer-guidelines .